2011
DOI: 10.1063/1.3583657
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of reduction of deep levels and surface passivation on carrier lifetimes in p-type 4H-SiC epilayers

Abstract: Temperature dependent recombination dynamics in InP/ZnS colloidal nanocrystals Appl. Phys. Lett. 101, 091910 (2012) Intrinsic defect in BiNbO4: A density functional theory study J. Appl. Phys. 112, 043706 (2012) The CuInSe2-CuIn3Se5 defect compound interface: Electronic structure and band alignment Appl. Phys. Lett. 101, 062108 (2012) Investigation of deep-level defects in conductive polymer on n-type 4H-and 6H-silicon carbide substrates using I-V and deep level transient spectroscopy techniques Impacts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…The surface recombination velocity on p-type 4H-SiC, however, may be still high. 39 The distribution of surface state density must be different near the conduction and valence bands. In addition, the direction of surface band bending is opposite, and the position of the surface Fermi level must be different for n-and p-type epilayers.…”
Section: B Lifetime Controlmentioning
confidence: 99%
“…The surface recombination velocity on p-type 4H-SiC, however, may be still high. 39 The distribution of surface state density must be different near the conduction and valence bands. In addition, the direction of surface band bending is opposite, and the position of the surface Fermi level must be different for n-and p-type epilayers.…”
Section: B Lifetime Controlmentioning
confidence: 99%
“…Silicon carbide (SiC) bipolar devices are considered as candidates of such power devices [1]. p-type SiC is a key material for development of bipolar SiC devices, and for any bipolar devices, control of the carrier lifetime in epilayers is strongly important [2][3][4][5]. However, studies for deep levels which affect the carrier lifetime in p-type 4H-SiC have been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that this phenomenon is caused by the enhanced Auger recombination in the f-SiC sample when the incident power density on the sample is increased. 29 In particular, it has been observed that 30 a fast decay component emerges during free carrier absorption (FCA) measurement on SiC at elevated injection levels, where this fast decay channel is attributed to band-to-band Auger recombination. Moreover, it is well known that the rate of Auger recombination is proportional to the cube 31 of the total carrier densities, i.e., n 0 + Δ n , where Δ n refers to the density of nonequilibrium carriers.…”
Section: Resultsmentioning
confidence: 99%